Pengaruh Cadangan Devisa, PDB dan Kurs Dollar Amerika Serikat Terhadap Impor Bahan Baku Industri di Indonesia - Kurniawati, Fitri; Suresmiathi D., Anak Agung Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 7, Juli 2015 (pp.746 - 872), 2015)
Most of the industries in Indonesia using raw materials imported from another countries. The development imports of industrial raw materials in Indonesia always increase higher than the imports of consumer goods and capital goods to domestic demand. The purpose of this study to determine the impact of foreign exchange reserves, gross domestic product and US dollar exchange rate toward import of industrial raw materials in Indonesia. The data research used is secondary data for period 1994-2013. The data analysis technique used is double linear regression with Eviews application program.The analysis result shows that simultaneously for foreign exchange reserves, gross domestic product and the US dollar exchange rate had a significant impact on industrial raw material imports. Partial test results in gross domestic product is the significant positive effect but foreign exchange reserves no significant effect on the import of industrial raw materials due to foreign exchange reserves are used for foreign debt payments and the level of imports is strongly influenced by the economic conditions in Indonesia, while the US dollar exchange rate significant negative effect on industrial raw material imports. Gross domestic product is the dominant independent variable effect on industrial raw material imports in Indonesia from analysis of standardized coefficient beta.
Keywords: Foreign Exchange Reserves, Gross Domestic Product, US Dollar Exchange Rate, and Import